Top-down control of soil fungal community composition by a globally distributed keystone consumer - Crowther, Thomas W; Stanton, David W G; Thomas, Stephen M; A'Bear, A Donald; Hiscox, Jennifer; Jones, T Hefin; Vorísková, Jana; Baldrian, Petr; Boddy, Lynne (Ecology, 2013)
The relative contribution of top-down and bottom-up processes regulating primary decomposers can influence the strength of the link between the soil animal community and ecosystem functioning. Although soil bacterial communities are regulated by bottom-up and top-down processes, the latter are considered to be less important in structuring the diversity and functioning of fungal-dominated ecosystems. Despite the huge diversity of mycophagous (fungal-feeding) soil fauna, and their potential to reverse the outcomes of competitive fungal interactions, top-down grazing effects have never been found to translate to community-level changes. We constructed soil mesocosms to investigate the potential of isopods grazing on cord-forming basidiomycete fungi to influence the community composition and functioning of a complex woodland soil microbial community. Using metagenomic sequencing we provide conclusive evidence of direct top-down control at the community scale in fungal-dominated woodland soil. By suppressing the dominant cord-forming basidiomycete fungi, isopods prevented the competitive exclusion of surrounding litter fungi, increasing diversity in a community containing several hundred fungal species. This isopod-induced modification of community composition drove a shift in the soil enzyme profile, and led to a restructuring of the wider mycophagous invertebrate community. We highlight characteristics of different soil ecosystems that will give rise to such top-down control. Given the ubiquity of isopods and basidiomycete fungi in temperate and boreal woodland ecosystems, such top-down community control could be of widespread significance for global carbon and nutrient cycling.
Keywords: Fungi; Gene Expression Regulation, Enzymologic; Gene Expression Regulation, Fungal; regulace genové exprese u hub; půdní mikrobiologie; Fungal Proteins; houby; Isopoda; Animals; půda; Soil Microbiology; fungální proteiny; zvířata; regulace genové exprese enzymů; Soil